2020
DOI: 10.1101/2020.01.09.900134
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bayesian genomic models boost prediction accuracy for resistance againstStreptococcus agalactiaein Nile tilapia (Oreochromus nilioticus)

Abstract: Streptococcosis due to Streptococcus agalactiae is a major bacterial disease in Nile tilapia, and development of the resistant genetic strains can be a sustainable approach towards combating this problematic disease. Thus, a controlled disease trial was performed on 120 full-sib families to i) quantify and characterize the potential of genomic selection for S. agalactiae resistance in Nile tilapia and to ii) select the best genomic model and optimal SNP-chip for this trait.In total, 40 fish per family (15 fish… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Although intraperitoneal route bypassed the natural immune barriers, it demonstrated higher additive genetic variation and heritability, compared to the cohabitation route of infection. The heritability for S. agalactiae resistance in Nile tilapia has been estimated previously by various authors using both pedigree (LaFrentz et al., 2016; Lin, 2016; Craig A Shoemaker, et al., 2017; Sukhavachana et al., 2019) and genomics (Joshi et al., 2020). These estimates vary from 0.13 to 0.32 and provide enough evidence for the possibility of genetic selection for Streptococcus resistance, but the genetic correlation of ~0 between S. agalactiae and S. iniae (Shoemaker, et al., 2017) calls for specialised challenge tests for each strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although intraperitoneal route bypassed the natural immune barriers, it demonstrated higher additive genetic variation and heritability, compared to the cohabitation route of infection. The heritability for S. agalactiae resistance in Nile tilapia has been estimated previously by various authors using both pedigree (LaFrentz et al., 2016; Lin, 2016; Craig A Shoemaker, et al., 2017; Sukhavachana et al., 2019) and genomics (Joshi et al., 2020). These estimates vary from 0.13 to 0.32 and provide enough evidence for the possibility of genetic selection for Streptococcus resistance, but the genetic correlation of ~0 between S. agalactiae and S. iniae (Shoemaker, et al., 2017) calls for specialised challenge tests for each strain.…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted using two lines of the commercial GenoMar Supreme Tilapia (GST®) breeding nucleus in the Philippines. The “selected line” comprised the fish selected for Streptococcus agalactiae [Ib serotype] (Joshi et al., 2020) resistance. Top animals were selected based on estimated breeding values (EBVs) for S. agalactiae resistance from the breeding nucleus for one generation (Lin, 2016) and randomly mated for 2 generations to produce the selected line.…”
Section: Methodsmentioning
confidence: 99%
“…Although prediction models such as GBLUP and Bayesian alphabet have been considered for genomic prediction of streptococcosis resistance in Nile tilapia (Joshi et al . 2020; Lu et al . 2020), the genetic architecture may not be the same in red tilapia.…”
Section: Resultsmentioning
confidence: 99%
“…a heritability of 0.27 was estimated by Sukhavachana et al (2019). Joshi et al, (2020b) reported genomic heritabilities for resistance against S. agalactiae in Nile tilapia ranging from 0.15 to 0.26. Significant genetic variation has also been detected for resistance against Flavobacterium columnare (Wonmongkol et al, 2018) and Streptococcus iniae (LaFrentz et al, 2016;Shoemaker et al, 2017), indicating the potential for improving survival against bacterial outbreaks by using artificial selection.…”
Section: Main Traits Genetic Parameters and Genotype By Environment mentioning
confidence: 99%
“…Furthermore, univariate and multivariate genomic selection approaches have also been tested using dense SNP genotypes for growth-and disease resistancerelated traits (e.g. Streptococcus resistance), showing an increase in prediction accuracy, when compared with conventional pedigree-based genetic evaluation methods (Joshi et al, 2020c(Joshi et al, , 2019. These results indicate the benefits of genomic evaluations for the genetic improvement of these populations.…”
Section: Qtl Mapping Gwas and Genomic Selectionmentioning
confidence: 99%